2010
DOI: 10.1371/journal.pone.0009579
|View full text |Cite
|
Sign up to set email alerts
|

A New Adenovirus Based Vaccine Vector Expressing an Eimeria tenella Derived TLR Agonist Improves Cellular Immune Responses to an Antigenic Target

Abstract: BackgroundAdenoviral based vectors remain promising vaccine platforms for use against numerous pathogens, including HIV. Recent vaccine trials utilizing Adenovirus based vaccines expressing HIV antigens confirmed induction of cellular immune responses, but these responses failed to prevent HIV infections in vaccinees. This illustrates the need to develop vaccine formulations capable of generating more potent T-cell responses to HIV antigens, such as HIV-Gag, since robust immune responses to this antigen correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
55
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 30 publications
4
55
0
Order By: Relevance
“…Capitalizing upon those findings, we have developed an Ad5-based vaccine platform that expresses a TLR agonist derived from E. tenella (i.e., recombinant Eimeria antigen [Ad5-GFP/rEA]). We have shown that vaccine cocktails containing the rEA-expressing Ad5 can induce heightened activation of innate immune responses compared to that found with controls when administered via the intravascular or intramuscular route (3). These responses include the induction of systemic cytokines and chemokines as well as increased activation/maturation of macrophage, DC, NK cell, and NKT cell populations in both the liver and the spleen.…”
Section: Vol 18 2011 Sublingual Ad5 Vaccine Elicits Mucosal T-cell mentioning
confidence: 91%
See 1 more Smart Citation
“…Capitalizing upon those findings, we have developed an Ad5-based vaccine platform that expresses a TLR agonist derived from E. tenella (i.e., recombinant Eimeria antigen [Ad5-GFP/rEA]). We have shown that vaccine cocktails containing the rEA-expressing Ad5 can induce heightened activation of innate immune responses compared to that found with controls when administered via the intravascular or intramuscular route (3). These responses include the induction of systemic cytokines and chemokines as well as increased activation/maturation of macrophage, DC, NK cell, and NKT cell populations in both the liver and the spleen.…”
Section: Vol 18 2011 Sublingual Ad5 Vaccine Elicits Mucosal T-cell mentioning
confidence: 91%
“…A mouse multiplex-based assay including IL-6, IL-12(p40), monocyte chemoattractant protein 1 (MCP-1), macrophage inflammatory protein 1␤ (MIP-1␤), keratinocyte-derived chemokine (KC), and RANTES was used per the manufacturer's instructions (Bio-Rad, Hercules, CA) to determine the indicated cytokine/chemokine plasma concentrations via Luminex 100 technology (Luminex, Austin, TX) as previously described (3). (SMLN preparations included cells derived from mandibular lymph nodes, accessory mandibular lymph nodes, and the superficial parotid lymph node [31]) was determined using IFN-␥ ELISpot analysis (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…These EAT-2-expressing Ad vectors were fully viable, grew to high titers, and were purified and quantified exactly as done for conventional [E12]Ad vaccines (25). To analyze the maximal impact that Ad-EAT2 expression might have upon innate immune responses, we administered Ad-EAT2 into C57BL/6 mice and measured the levels of cytokines and chemokines in the plasma 6 h postinjection (hpi), a time point we have previously demonstrated to be when maximal induction of proinflammatory cytokines and chemokines occurs after Ad vector administration (9,27,28). Administration of the Ad-EAT2 vector into C57BL/6 mice resulted in induction of significantly higher plasma levels of RANTES and MCP-1 at 6 hpi as directly compared with those of mice injected identically and treated with an Ad-GFP control vector (Fig.…”
Section: Eat-2-expressing Ad Vectors Enhance Ad Vector-induced Innatementioning
confidence: 99%
“…We wished to evaluate the potential of improving vaccination efficacy by presenting a target Ag while simultaneously activating novel arms of the mammalian immune system. Whereas in previous studies we and others have explored the potential of modifying TLRdependent innate immune responses to facilitate improved efficacy of virus-based vaccines (9,10), in this study we set out to determine if targeted manipulation of the signaling lymphocytic activation molecule (SLAM) family of receptors pathway could also facilitate improved induction of Ag-specific, adaptive immune responses by vaccine platforms.…”
mentioning
confidence: 99%
“…Ad5-based vaccines are attractive for a multitude of reasons, including their broad human cell tropism, relative ease of manufacturing for scaled production, and low potential for adverse side effects (1). Additionally, numerous studies have demonstrated the tremendous ability of Ad5-based vaccines to create robust, transgene-specific cell-mediated immunity against antigens derived from pathogens, such as HIV (2)(3)(4)(5)(6)(7)(8), the malaria parasite (9,10), and Mycobacterium tuberculosis (11,12), as well as many tumor-associated antigens (13)(14)(15)(16)(17). Although the advantages of these vaccines are abundant, there has been some hesitation toward their practical use due to the high prevalence of preexisting Ad5 immunity in the human population (18)(19)(20).…”
mentioning
confidence: 99%